Communication Strategy of BPBD of East Java Province in Reducing Disaster Risk: Case Study of Disaster Prevention Socialization - Solihin Solihin; Redi Panuju; Farida Farida; Zulaikha Zulaikha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study focuses on the effectiveness of the communication strategy of the East Java Provincial Disaster Management Agency (BPBD) in disaster socialization. Using a qualitative approach and case study method, this study evaluates the selection of communicators, target setting, messages, and communication media used. The results of the study indicate that selecting the right communicator, including collaboration with the Regency/City BPBD and experts, significantly increases public understanding of disaster risk. In addition, adjusting messages according to local characteristics and disaster vulnerability levels is effective in clarifying information to the public. Social media and innovations such as the Disaster Management Education Car (MOSIPENA) and the Disaster Education Tent (TEMPINA) have been proven to expand reach and increase community involvement. The novelty of this study includes an in-depth analysis of the strategy for selecting communicators and cross-sectoral collaboration in disaster communication, as well as the adjustment of innovative and specific messages according to the characteristics of disaster-prone areas. This study also highlights the use of technology and social media to improve the effectiveness of socialization, as well as the implementation of innovative methods in delivering disaster information. These findings offer a practical model for more effective disaster socialization and open up opportunities for further research in the development of disaster communication methods.